Coaches of athletes with a physical disability: a look at their learning experiences - McMaster, S.; Culver, D.; Werthner, P. (Qualitative Research in Sport, Exercise and Health, 2012)
Literature has shown that research on coaches of athletes with a physical disability is lacking. The purpose of this study is to examine the learning experiences of coaches in disability sport. Five coaches participated in this study. Data included two semi-structured interviews and two non-participant observation sessions with each coach. Thematic analysis was employed using theory of human learning as a theoretical framework. Results indicated three main themes influencing the coaches` learning and development: (a) their biographies, (b) how they chose to learn (i.e. through formal, non-formal and informal learning situations) and (c) the learning opportunities provided by their sport. The coaches noted the usefulness of varied learning situations, and identified a lack of resources and few non-formal and formal learning opportunities specific to disability sport.